Activation Temperature Study of Precipitated Fe/SiO2 Catalyst for Fischer-Tropsch Synthesis - Qian, Weixin; Zhang, Haitao; Sun, Qiwen; Liu, Yongdi; Ying, Weiyong; Fang, Dingye (Asian Journal of Chemistry, 2014)
The adsorption performance of H2 and CO on a co-precipitated Fe/SiO2 catalyst was studied by H2-TPD, CO-TPD. XRD and Mössbauer spectrum to analyze the effect of activation temperature on the reaction performance and the composition of iron phases on catalyst surface. The results showed that hydrogen probably existed as the most stable CH and OH species on CO reduced catalysts, most of CO adsorbed as a dissociate state on CO reduced Fe/SiO2 catalyst. On the reduced catalyst, the diffraction peaks intensity of iron carbides increased obviously while that of Fe3O4 diffraction peaks slightly reduced. On the used catalyst, the iron phases were mainly constituted by Fe3O4 and iron carbides. A higher activation temperature led to higher activity of catalyst, meanwhile, the weight fractions of CH4 and C2-8 increased slightly while C9+ decreased with increasing activation temperatures.